Cardiac-specific renalase overexpression alleviates CKD-induced pathological cardiac remodeling in mice - Wang, Yi; Bai, Linnan; Wen, Jiejun; Zhang, Fangfei; Gu, Sijie; Wang, Feng; Yin, Jianyong; Wang, Niansong (Frontiers in Cardiovascular Medicine, 2022)
Introduction CKD-induced pathological cardiac remodeling is characterized by myocardial hypertrophy and cardiac fibrosis. The available therapeutic options are limited, it is thus urgently needed to identify novel therapeutic targets. Renalase (RNLS) is a newly discovered protein secreted by the kidney and was found beneficial in many renal diseases. But whether it exerts protective effects on cardiac remodeling in CKD remains unclear. Methods RNLS knockout (KO) and wild-type (WT) mice were both used to build CKD models and the adeno-associated virus (AAV9) system was used to overexpress RNLS cardiac specifically. Echocardiography was performed to detect cardiac structural changes every 6 weeks until 18 weeks post-surgery. High throughput sequencing was performed to understand the underlying mechanisms and the effects of RNLS on cardiac fibroblasts were validated in vitro. Results Knockout of RNLS aggravated cardiac remodeling in CKD, while RNLS cardiac-specific overexpression significantly reduced left ventricular hypertrophy and cardiac fibrosis induced by CKD. The following RNA-sequencing analysis revealed that RNLS significantly downregulated the extracellular matrix (ECM) receptor interaction pathway, ECM organization, and several ECM-related proteins. GSEA results showed RNLS significantly downregulated several profibrotic biological processes of cardiac fibroblasts which were upregulated by CKD, including fibroblast proliferation, leukocyte migration, antigen presentation, cytokine production, and epithelial-mesenchymal transition (EMT). In vitro, we validated that RNLS reduced the primary cardiac fibroblast proliferation and α-SMA expression stimulated by TGF-β. Conclusion In this study, we examined the cardioprotective role of RNLS in CKD-induced cardiac remodeling. RNLS may be a potential therapeutic factor that exerts an anti-fibrotic effect in pathological cardiac remodeling.